Oberprielerius, a new genus for Anchonidium uniforme Voss, 1974, a microphthalmic species of Rhythirrinini (Coleoptera: Curculionidae: Cyclominae) from South Africa - Hlaváč, Peter; Borovec, Roman (Zootaxa, 2022)
A new genus, Oberprielerius gen. n., from the Republic of South Africa, is described for Anchonidium uniforme Voss, 1974 in the tribe Rhythirrinini Lacordaire, 1863 of the subfamily Cyclominae Schoenherr, 1826.